Influence of institutional innovation in the Peruvian avocado export sector - Valle Colchao, Manuel Elías (2022)
Institutional innovation aims at the confluence of public policies with the purpose of generating economic development for the productive sectors of a certain nation. The purpose of this research work is to analyze the impact of institutional innovation on the development of the Peruvian avocado export sector from 1961 to 2017. The methodological tools for research and development are the analysis of discrete structures and economic models. The basis of this art is based on the theory of export growth and the role of in export growth. In the main results, it was found that changes in the rules of the game (institutional innovation) inside and outside the Peruvian country promoted the development of the Peruvian avocado export sector. Allow innovation from the organizational and technological environment after the agrarian crisis. In this sense, the reversal of the agrarian crisis (institutional innovation) not only benefits the export of Peruvian avocados, but also completely changes the organizational and technological environment in which the industry operates to generate long-term competitiveness. According to the review of the current situation of the Peruvian avocado sector, no work was found that addresses the origin of the impact of institutional innovation in the sector, nor the relationship between the organizational environment and technology; this research is considered a contribution to the knowledge of future research.